FCC riser quick separation system： a review - Li, Zhi; Lu, Chun-Xi (Petroleum science, 2016)
The riser reactor is the key unit in the fluid catalytic cracking（FCC） process. As the FCC feedstocks become heavier, the product mixture of oil, gas and catalysts must be separated immediately at the outlet of the riser to avoid excessive coking. The quick separation system is the core equipment in the FCC unit. China University of Petroleum（Beijing） has developed many kinds of separation system including the fender-stripping cyclone and circulating-stripping cyclone systems, which can increase the separation efficiency and reduce the pressure drop remarkably. For the inner riser system, a vortex quick separation system has been developed. It contains a vortex quick separator and an isolated shell. In order to reduce the separation time, a new type of separator called the short residence time separator system was developed. It can further reduce the separation time to less than 1 s. In this paper, the corresponding design principles,structure and industrial application of these different kinds of separation systems are reviewed. A system that can simultaneously realize quick oil gas separation, quick oil gas extraction and quick pre-stripping of catalysts at the end of the riser is the trend in the future.